2008
DOI: 10.1212/01.wnl.0000303818.38960.44
|View full text |Cite
|
Sign up to set email alerts
|

Use of antihypertensives and the risk of Parkinson disease

Abstract: Current long-term use of calcium channel blockers was associated with a significantly reduced risk of a Parkinson disease diagnosis, while the risk was not materially altered for users of angiotensin converting enzyme inhibitors or beta-blockers and, with less statistical precision, for users of angiotensin II antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
172
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(179 citation statements)
references
References 32 publications
6
172
1
Order By: Relevance
“…DHPs are use-dependent antagonists of LTCCs that have a long history of success in the treatment of hypertension in humans 9 . In agreement with the propositions that LTCCs contribute to pathogenesis, retrospective epidemiological studies conducted in the United Kingdom 10 and Denmark 11 have revealed that the treatment of hypertension with DHPs that cross the blood-brain barrier diminish the observed risk of PD.…”
supporting
confidence: 65%
“…DHPs are use-dependent antagonists of LTCCs that have a long history of success in the treatment of hypertension in humans 9 . In agreement with the propositions that LTCCs contribute to pathogenesis, retrospective epidemiological studies conducted in the United Kingdom 10 and Denmark 11 have revealed that the treatment of hypertension with DHPs that cross the blood-brain barrier diminish the observed risk of PD.…”
supporting
confidence: 65%
“…Parkinson's disease, 35,36,62,63 whereas others did not find a significant effect. 64,65,66,67 However, the consensus based upon systematic review of all available literature is that treatment with calcium channel blockers does appear to reduce the risk of Parkinson's disease 68,69 although the mechanism by which they do so is not completely understood.…”
Section: Introductionmentioning
confidence: 83%
“…Calcium channel antagonists (CCAs), including the DHPs used in animal studies, are commonly used in clinical practice to treat hypertension, creating a potential database to be mined. A case-control study of hypertensive patients found a significant reduction in the observed risk of PD with CCA use, but not with medications that reduce blood pressure in other ways (9). More recently, a large Danish data set has been examined (100 …”
Section: Surmeier Et Almentioning
confidence: 99%